Crystal structure of diaqua-trans-dicinnamato-dihexamethylenetetraminecobalt(II) dihydrate, Co(C6H12N4)2(C9H7O2)2(H2O)2 · 2H2O - Zhu H.-L. (Zeitschrift für Kristallographie - New Crystal Structures, 2003)
C30H46CoN8O8, monoclinic, P121/c1 (No. 14), a = 12.779(3) Å, b = 10.938(2) Å, c = 12.218(2) Å, β = 97.56(3)°, V = 1693.0 Å3, Z = 2, Rgt(F) = 0.085, wRref(F2) = 0.201, T = 293 K.